2010
DOI: 10.1111/j.1464-410x.2010.09909.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved cancer specific‐survival in patients with carcinoma invading bladder muscle expressing cyclo‐oxygenase‐2

Abstract: Immunoreactivity was categorized as positive if COX-2 staining was present in > 5% tumour cells. RESULTSThe expression of COX-2 was not influenced by tumour stage, grade or nodal status, nor any other parameters. The risk factors that influenced disease-specific survival in carcinoma invading bladder muscle on multivariate analysis were lymph node status (hazards ratio, HR = 2.46 for N1, P = 0.001, HR = 2.90 for N2, P < 0.001, HR = 5.19 for N3, P = 0.012), use of neoadjuvant chemotherapy (HR = 3.54; P = 0.004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
3
7
1
Order By: Relevance
“…Twenty publications on COX2 expression and bladder cancer prognosis were identified through the literature review (Table S1) [12][31]. Three of them lacked prognostic data, two overlapped with other larger studies and four included patient cohorts that did not meet the eligibility criteria outlined earlier, leaving 11 evaluable publications [12]–[14], [19], [21][25], [28], [29] plus the current study for the meta-analysis (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty publications on COX2 expression and bladder cancer prognosis were identified through the literature review (Table S1) [12][31]. Three of them lacked prognostic data, two overlapped with other larger studies and four included patient cohorts that did not meet the eligibility criteria outlined earlier, leaving 11 evaluable publications [12]–[14], [19], [21][25], [28], [29] plus the current study for the meta-analysis (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Three of them lacked prognostic data, two overlapped with other larger studies and four included patient cohorts that did not meet the eligibility criteria outlined earlier, leaving 11 evaluable publications [12]–[14], [19], [21][25], [28], [29] plus the current study for the meta-analysis (Figure S4). Studies were classified by the tumor subtype(s) they reported on (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a population of 266 MIBC patients, individuals with positive immunostaining of cyclo-oxygenase-2 (COX-2) have higher DSS ( p = 0.006) and recurrence-free survival ( p = 0.003) rates than those with negative staining [17]. However, another study of 46 MIBC patients undergoing cystectomy failed to show statistically significant association between COX-2 positive staining and survival [18] but did find a negative correlation between COX-2 protein levels and the extent of lymph node metastasis ( p = 0.008) [18].…”
Section: Prognostic Biomarkers That Identify High-risk Patientsmentioning
confidence: 99%
“…However, another study of 46 MIBC patients undergoing cystectomy failed to show statistically significant association between COX-2 positive staining and survival [18] but did find a negative correlation between COX-2 protein levels and the extent of lymph node metastasis ( p = 0.008) [18]. In contrast to the result in MIBC patients [17], lower COX-2 protein expression in individuals with squamous cell carcinomas had higher recurrence-free (hazard ratio (HR) = 2.1, p = 0.031) and DSS (HR = 2.3, p = 0.046) rates [19]. D-type cyclins are also prognostic markers in advanced bladder cancer.…”
Section: Prognostic Biomarkers That Identify High-risk Patientsmentioning
confidence: 99%